State abortion restrictiveness and prevalence of intimate partner violence and domestic violence among recently birthing black and white individuals - Katherine Neff; Katherine Neff; Katherine Neff; Stephanie V. Hall; Stephanie V. Hall; Rieham Owda; Rieham Owda; Andrea Pangori; Andrea Pangori; Kara Zivin; Kara Zivin; Kara Zivin; et al. (Frontiers in Reproductive Health)
ObjectivesIntimate partner violence (IPV) and non-intimate domestic violence (DV) during pregnancy may result in poor maternal and infant health outcomes. Whether state-level abortion restrictions, enacted by many states even prior to the 2022 Dobbs v. Jackson Women's Health Organization decision, are associated with IPV/DV remains unknown. This study aimed to investigate the relationship between IPV/DV during pregnancy and abortion restrictions among Black and White birthing people.Study designWe analyzed 2020 data from 36 states participating in the CDC Pregnancy Risk Assessment Monitoring System representing 1,931,458 deliveries of which 1,368,237 deliveries (70.84%) are from Black and White birthing individuals. We divided states into restrictive (N = 17) and less restrictive (N = 19) based on a modified Guttmacher Abortion Policy Hostility Index. We used weighted logistic regression to assess the relationship between state abortion restrictiveness and self-reported IPV/DV.ResultsOverall, birthing individuals in restrictive states had higher odds of reporting IPV/DV during pregnancy than those in less restrictive states (aOR: 1.36, 95% CI: 1.15–1.60). Within racial groups, we found that Black birthing individuals in restrictive states had higher odds of reporting IPV/DV than Black birthing individuals in less restrictive states (aOR:1.75, 95% CI: 1.24–2.47). We saw a similar relationship for White birthing individuals (aOR:1.50, 95% CI: 1.17–1.94).DiscussionEven when access to abortion was federally protected, individuals in restrictive states had higher odds of experiencing IPV/DV than those in less restrictive states, particularly among Black individuals. These findings suggest possible detrimental impacts of abortion restrictions and their potential to worsen existing health inequities.